A substitution mutation in cardiac ubiquitin ligase, FBXO32, is associated with an autosomal recessive form of dilated cardiomyopathy. Issue 1 (December 2016) - Al-Hassnan, Zuhair; Shinwari, Zarghuna; Wakil, Salma; Tulbah, Sahar; Mohammed, Shamayel; Rahbeeni, Zuhair; Alghamdi, Mohammed; Rababh, Monther; Colak, Dilek; Kaya, Namik; Al-Fayyadh, Majid; Alburaiki, Jehad
Abstract Background Familial dilated cardiomyopathy (DCM) is genetically heterogeneous. Mutations in more than 40 genes have been identified in familial cases, mostly inherited in an autosomal dominant pattern. DCM due to recessive mutations is rarely observed. In consanguineous families, homozygosity mapping and whole exome sequencing (WES) can be utilized to identify the genetic defects in recessively inherited DCM. Methods In a consanguineous family with four affected siblings with severe DCM, we combined homozygosity mapping, linkage analysis and WES, to uncover the genetic defect. Results A region of homozygosity (ROH) on chromosome 8q24.13–24.23 was found to be shared by all of the four affected siblings. WES detected ~47, 000 variants that were filtered to a homozygous mutation (p.Gly243Arg) in theFBXO32 gene, located within the identified ROH. The mutation segregated with the phenotype, replaced a highly-conserved amino acid, and was not detected in 1986 ethnically-matched chromosomes.FBXO32, which encodes a muscle-specific ubiquitin ligase, has been implicated in the pathogenesis of cardiomyopathy through the ubiquitin proteasome system (UPS). In addition, FBXO32 -knockout mice manifest with cardiomyopathy. Screening the index patient for all of the WES variants in 48 genes known to be implicated in hypertrophic and dilated cardiomyopathy was negative. Conclusions Our data suggest thatFBXO32 is a candidate gene for recessive DCM. Acting as a cardiac ubiquitin ligase, mutatedFBXO32 could perturb the degradation of target proteins in the UPS, the impairment of which has been observed in cardiomyopathy. Our work proposes that genes encoding other ubiquitin ligases could also be implicated in familial cardiomyopathy.